Women's asset ownership evidence from Georgia; Mongolia; and Cavite, Philippines. - Joshi, Kaushal ([Manila] Asian Development Bank, 2019)
It draws on findings from pilot surveys in Georgia, Mongolia, and the Philippines. Survey results suggest substantial gender gaps in ownership across different types of assets and countries. These variations confirm the importance of understanding the social norms governing gender roles and laws that can facilitate or impede womens asset ownership. Womens rights to own and control assets are critical for securing gender equity in economic participation and opportunity, and delivering on the Sustainable Development Goals.
Keywords: Social rights -- Philippines; Gender equality; Electronic books